Tool for Assessment of Climate Change “Sense” TACCS - طقس ( version 1.0) - Moujahed, Nizar (International Center for Agricultural Research in the Dry Areas, 2024)
This tool presents a detailed questionnaire designed to quantitatively assess an organization's perception, awareness, and determination towards climate change through five main components, covering personal knowledge and opinions on climate change, training received, organizational involvement, communication strategies, and the influence of cultural, religious, and political factors. Developed to evaluate the trilogy of perception, consciousness, and determination regarding climate change within administrative bodies, civil society, or agricultural organizations, the tool employs these five components to calculate a global index, the Perception, Consciousness, and Determination Index (PCD). The PCD index aids in assessing the current state, tracking evolution over time, or measuring changes before and after climate change projects, enabling policymakers to select suitable programs and plan actions to enhance climate change perception and sensitivity, leading to effective adaptation and mitigation strategies. Currently, TACCS (version 1.0) is being tested within select professional groups.